Oral food challenges in children - Hye Yung Yum; Hyeon Jong Yang; Kyung Won Kim; Tae Won Song; Woo Kyung Kim; Jung Hee Kim; Kang Mo Ahn; Hyun Hee Kim; Soo Young Lee; Bok Yang Pyun (Korean Pediatric Society, 2011)
Many patients assume that allergic reactions against foods are responsible for triggering or worsening their allergic symptoms. Therefore, it is important to identify patients who would benefit from an elimination diet, while avoiding unnecessary dietary restrictions. The diagnosis of food allergy depends on the thorough review of the patients's medical history, results of supplemented trials of dietary elimination, and in vivo and in vitro tests for measuring specific IgE levels. However, in some cases the reliability of such procedures is suboptimal. Oral food challenges are procedures employed for making an accurate diagnosis of immediate and occasionally delayed adverse reactions to foods. The timing and type of the challenge, preparation of patients, foods to be tested, and dosing schedule should be determined on the basis of the patient's history, age, and experience. Although double-blind, placebo-controlled food challenges(DBPCFC) are used to establish definitively if a food is the cause of adverse reactions, they are time-consuming, expensive and troublesome for physician and patients. In practice, An open challenge controlled by trained personnel is sufficient especially in infants and young children. The interpretation of the results and follow-up after a challenge are also important. Since theses challenges are relatively safe and informative, controlled oral food challenges could become the measure of choice in children.